Business in the 21st century : a sustainable approach - Berrones-Flemmig, Claudia Nelly; Contreras, Francoise; Dornberger, Utz (Emerald Publishing Limited, 2022)
How can businesses around the world incorporate the Sustainable Development Goals (SDGs) into their models, policies and practices? The editors of Business in the 21st Century help answer this by bringing together scholars from around the world with chapters examining various industries ranging from finance, hospitality, aviation, tourism, food production and more. With international perspectives, business concepts such as HRM, employee wellbeing, leadership and digitalisation are also researched within the framework of the SDGs. Insights from how to implement such policies in a post-pandemic world are introduced to help businesses navigate the biggest disruption they have faced in decades. Business in the 21st Century provides a valuable framework for scholars, managers, leaders and business stakeholders to help navigate the incorporation of SDGs into the business world, shape strategy, improve practices and create a better business future.